Multi-layered solid-PCM thermocline thermal storage for CSP. Numerical evaluation of its application in a 50 MWe plant. (September 2015) - Galione, P.A.; Pérez-Segarra, C.D.; Rodríguez, I.; Torras, S.; Rigola, J.
Highlights: MLSPCM concept of thermal storage for CSP is evaluated for a 50 MWe CSP plant. Comparison against solid-filled thermocline and 2-tank systems is performed. Numerical analysis is used for the thermal evaluation of thermocline configurations. Evaluation of isolated TES as well as integrated into a CSP plant are performed. Results indicate that MLSPCM is an interesting alternative for storage in CSP plants. Abstract: Thermocline storage concept is considered as a possible solution to reduce the cost of thermal storage in concentrated solar power (CSP) plants. Recently, a multi-layered solid-PCM (MLSPCM) concept—consisting of a thermocline-like tank combining layers of solid and phase change filler materials—has been proposed. This approach was observed to result in lower thermocline degradation throughout charge/discharge cycles, due to the thermal buffering effect of the PCM layers located at both ends of the tank. MLSPCM prototypes designed for a pilot scale plant were numerically tested and compared against other designs of single-tank thermocline systems, such as: solid-filled thermocline, tanks filled with a single encapsulated PCM and cascaded-PCM configurations. Results showed promising results of the MLSPCM configurations for their potential use in CSP plants. In this work, the MLSPCM concept is used for designing a thermal energy storage (TES) system for a CSP plant with the dimensions and operating conditions of a parabolic trough plant of 50 MWe, similar to Andasol 1 (Granada, Spain). The performance evaluation of each of the proposed prototypes is virtually tested by means of a numerical methodology which considers the heat transfer and fluid dynamics phenomena present in these devices. Two sets of cases are considered, one with the objective of testing the TES systems individually, by defining specific operating conditions and taking the systems to a periodic steady state; and another, aiming to evaluate their performance after several days of operation in a CSP plant, in which the weather variability and the thermal behavior of the tank walls and foundation are simulated. Thermal performance parameters, such as total energy and exergy stored/released and the efficiency in the use of the storage capacity, are calculated and compared with those obtained by other thermocline-like configurations (single-solid and single-PCM), and with a reference 2-tank molten-salt system. Obtained results allow to continue considering the MLSPCM concept as an interesting alternative for thermal storage in CSP facilities.